2019
DOI: 10.24996/ijs.2019.60.6.3
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Total Body Mass between Pre and Postmenopausal Women in Mosul City

Abstract: In this research, we discussed bone density for women taking into consideration the method of research, we measure the total body mass of women in premenopausal and comparing it with postmenopausal, since the amount of the bone mineral content and bone mineral density, fat mass and lean mass.A cross sectional study conducted at DXA laboratory, Physiology Department, College of Medicine, University of Ninevah, Mosul-Iraq from Jan. 1 - Dec. 31, 2013. Since 174 healthy women recruited from reviewing of college me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…The imbalance between resorption and production rates brought on by menopause and aging increases the chance of fracture (1). Studies found that bone mass decrease by 1% per year from midlife onwards (6). Due to the strong structural similarities between skeletal bones and teeth, both can be impacted by the same metabolic disruptions, leading one to conclude that the same pathways could cause both bone loss and tooth decay (7).…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance between resorption and production rates brought on by menopause and aging increases the chance of fracture (1). Studies found that bone mass decrease by 1% per year from midlife onwards (6). Due to the strong structural similarities between skeletal bones and teeth, both can be impacted by the same metabolic disruptions, leading one to conclude that the same pathways could cause both bone loss and tooth decay (7).…”
Section: Introductionmentioning
confidence: 99%